2021
DOI: 10.3390/vaccines9040363
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Quality Is a Key Factor to Determine Thermal Stability of Commercial Newcastle Disease (ND)Vaccines

Abstract: Vaccination against Newcastle disease (ND), a devastating viral disease of chickens, is often hampered by thermal inactivation of the live vaccines, in particular in tropical and hot climate conditions. In the past, “thermostable” vaccine strains (I-2) were proposed to overcome this problem but previous comparative studies did not include formulation-specific factors of commercial vaccines. In the current study, we aimed to verify the superior thermal stability of commercially formulated I-2 strains by compari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…1). Although conditions vary considerably between studies, these virus decay trends are in general agreement with those reported by others [36][37][38][39][40][41][42][43]. Therefore, an inactivation reagent utilized at the time of sample collection is ideal to alleviate concerns about transmission during shipping procedures and facilitate testing at lower containment facilities.…”
Section: Discussionsupporting
confidence: 87%
“…1). Although conditions vary considerably between studies, these virus decay trends are in general agreement with those reported by others [36][37][38][39][40][41][42][43]. Therefore, an inactivation reagent utilized at the time of sample collection is ideal to alleviate concerns about transmission during shipping procedures and facilitate testing at lower containment facilities.…”
Section: Discussionsupporting
confidence: 87%
“…It was previously reported that 58% of Tanzanian households are using I-2 and 42% are using LaSota [ 60 ]. The I-2 strain was recommended for ND vaccination in hot climates since it minimizes temperature-induced degradation [ 61 ]. As recently suggested by Dimitrov [ 1 ], the efficacy of current live attenuated vaccines against currently circulating strains of NDV and vaccine application failure should be considered when designing new, more effective vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…The RMC of the NDV-VFD vaccine was detected using thermogravimetric analysis (Merivaara et al 2021 ; Osman et al 2021 ; Regis et al 2021 ). To determine the RMC after drying, eight vials of each vaccine preparation were weighed before and after drying at 80℃ for 2 h without a stopper.…”
Section: Methodsmentioning
confidence: 99%